Ler e escrever: uma revisão integrativa de trabalhos acadêmicos sobre o Programa da SEE/SP - Miguel, Yara Maria (2016)
The present research investigated the results of post-graduation academic researches about the SEESP program “Programa Ler e Escrever”, which had as a purpose the development of projects aiming to revert the illiteracy and precarious literacy rates among students from the 1st Cycle of the basic education, inside São Paulo State’s teaching network. The objective was to identify and analyze the results of 16 researches (among master’s and doctorate’s degree) that had as primary object of study the “Programa Ler e Escrever” (signaled in the titles of the researches), submitted to a public defense between 2010 and January 2016. This research adopted a methodological approach based on integrative revision, which seeks the critical evaluation and the synthesis of evidences, both qualitative and quantitative, of the researched area. It was found that the researches were of documental and empirical nature, being their results organized in accordance with the data production sources: teachers; teachers and students, teachers and coordinators; coordinators and student researchers. As the results of the documental evidences, the research evinced a need of more explicit theoretical basis in didactical orientations offered to the teachers, also noting a critical resistance from the teachers in using these didactical materials. About the results of the empirical evidences about teachers, these pointed to the reframing of the classroom practices, while those evidences related to teachers, coordinators and students reveal that they attribute quality to the didactic material’s activities. The integrative revision shows disparate results concerning some objects and same subjects, but also shows a vision that integrates, without denying the negative aspects, the advances gradually achieved, reflected on the reading and writing learning process, consolidating the objective of the program “Programa Ler e Escrever”